The Challenge of Protecting the Wealth of Fauna in Africa - Lisna Novita; Nida Febriani; Rida Cahyanie; Dina Siti Logayah (FKIP, Universitas Palangka Raya, 2023)
This study analyzes the challenges to protecting the richness of fauna in Africa. In this study the authors used a qualitative approach as well as a literature study method or it can also be called a literature study, where during the data collection process it was carried out by digging up information that was relevant to the topic of the research being researched, namely through sources from journals, books, articles and sources from Internet. Africa's nature is known for its rich diversity of wildlife. The continent of Africa is a vast continent, with diverse ecosystems that include forests, deserts, mountains and rivers, thus creating a variety of habitats for the thousands of animal species that live there. But currently, many wild animals in Africa are endangered. This is certainly a challenge for Africa in protecting existing wildlife. Various things such as illegal hunting, loss of natural habitats, and human-animal conflicts often threaten the survival of wild animal species that live in Africa. Therefore, it is necessary to make efforts to save these animals from extinction